The Implementation of Student-Centred Learning in Teaching Reading at SMA 10 Luwu - Putri, Hardianti Eka; Atmowardoyo, Haryanto; Sulaiman, Iskandar (Celebes Journal of Language Studies, 2024)
In this millennial era, English has become the common language to use in supporting communication between people from different countries in worldwide. Therefore, the government simultaneously develops human resources in the education sector by submitting the English subject into the education curriculum as one of the significant subjects in the school. As one of the four skill aspects, reading skill is a significant skill for mastering English. The English teachers at school are challenged to prepare the best learning materials to stimulate students’ reading skill. Student-Centred Learning is believed as an effective way to support the material stimulating this skill. This study aims to investigate the implementation of Student-Centred Learning in teaching reading at SMA 10 Luwu. The data of this study were collected from interviews of both students and teachers which had been transcribed by the researcher and also from class observation results to investigate students’ engagement in reading class. The researcher used a qualitative research method to analyze the data which had been analyzed by utilizing the interactive model of data analysis which employs data collection, data condensation, data display, and conclusion. The results of this study lead to several points which are: (1) teachers’ understanding of the student-centred learning paradigm is quite well and SCL has been implemented roundly in SMA 10 Luwu despite several shortcomings that still occur in the learning process, (2) teachers mostly implement some methods of SCL which are auditory intellectually repetition (AIR) learning method, brainstorming method, cooperative script method, and cooperative integrated reading and composition (CIRC), and (3) the weakest aspect of reading engagement that should be highlighted is from cognitive aspects. Specifically, the point of students does not use comprehension strategies well. This is due to students’ low mastery of vocabulary.